THE IMPACT OF TURKEY’S POLICY ON REFUGEES (CASE STUDY OF SYRIAN REFUGEES) - Kadhafie, Muhammad; Haidar, Abdullah (Universitas Padjadjaran, 2026)
In the aftermath of World War II, the international community sought to establish a global order that guarantees the protection of human rights, formally declared through the 1948 Universal Declaration of Human Rights. Fundamental principles such as the right to life, the right to security, and freedom from torture became central to the international human rights regime. However, contemporary realities demonstrate that human rights violations persist, particularly in situations of armed conflict. The Syrian conflict, which began in 2011, has evolved into one of the largest humanitarian crises of the 21st century, forcing millions of civilians to flee their country in search of safety. Turkey, as Syria’s neighboring country and a state party to the 1951 Refugee Convention and its 1967 Protocol, has become the largest host country for Syrian refugees. Through its open-door policy and temporary protection regime, Turkey admitted millions of refugees within a relatively short period. While this policy reflects a humanitarian commitment, it has also generated significant political, economic, and social consequences within the host state. This article aims to analyze the impact of Turkey’s refugee policy on Syrian refugees, examining both its humanitarian dimension and its domestic and geopolitical implications. The study employs a descriptive qualitative approach based on literature review and policy analysis. The findings indicate that Turkey’s refugee policy represents a dynamic interaction between humanitarian responsibility and strategic national interests, producing multidimensional impacts on the country’s socio-economic stability and political landscape.